Analysis of Increasing Tourism Competitiveness in Selayar Islands Regency - Nawir Rahman; Annisa Ritri (Universitas Negeri Makassar, 2022)
This study aims to examine the potential and analyze the competitiveness of maritime tourism in the Selayar Islands Regency using the SWOT analysis method, as well as to find out the optimal strategy for increasing the competitiveness of marine tourism in the Selayar Islands Regency. This type of research is qualitative with a descriptive approach. Data collection techniques are carried out by observation, interviews, and documentation. The data analysis technique used consists of condensing data, presenting data and drawing conclusions. The results showed that the SWOT analysis model increased the competitiveness of marine tourism, namely having strength in the form of high social cohesion; good service standards; the natural wealth and diversity of marine biota in the Selayar Islands Regency. The strategy of the Selayar Islands Regency Tourism and Culture Office in increasing the competitiveness of marine tourism is the development of the tourist market; tourism product development; development through increasing human resources; developing quality and sustainable marine tourism networks and partnerships; increasing the quality and diversity of business products and tourism services.